Imag(in)ing War Trauma in Sakaguchi Ango's "The Idiot" and Ōe Kenzaburō's "Prize Stock". Issue 3 (2nd July 2016) - Stahl, David C.
ABSTRACT: According to trauma studies specialists such as Pierre Janet, Judith Herman, and Walter A. Davis, traumatic events and experiences cannot be known, understood, communicated, or learned from until they have been adequately constituted in language, symbol, and image. In this essay, I use Davis's concepts of "aesthetic cognition" and "vital images" to examine two scenes of extreme interpersonal violence. The first appears in "Hakuchi" ("The Idiot"), Sakaguchi Ango's 1946 story based on his personal experience of the fire-bombing attacks on Tokyo, and the second appears in "Shiiku" ("Prize Stock"), Nobel Prize-winning author Ōe Kenzaburō's debut work in which he represents integral aspects of his own overwhelming childhood experience of war and defeat. After introducing Davis's theoretical conceptions and providing background and context for the stories, I analyze and interpret the vital images showcased therein on interpersonal, nation-state, and international levels. In closing, I reflect on the valuable contributions of art to the constitution of critical knowledge and understanding of lived experiences of historical trauma and victimization.